Does Invasion of Eurasian Milfoil Myriophyllum spicatum Lead to a “Trophic Dead End” and Reduced Food Web Complexity in Gulf of Mexico Estuarine Food Webs? - Martin, Charles W.; Valentine, John F. (Frontiers in Environmental Science, 2019)
Estuaries of the northern Gulf of Mexico contain an abundance of habitat-forming submerged aquatic vegetation (SAV) that provide refuge and protection for a variety of freshwater, estuarine, and marine organisms. However, many of these estuaries now contain numerous exotic species, the ultimate impacts of which are unclear. In the Mobile-Tensaw Delta, located in the upper portion of Mobile Bay, Alabama (USA), Eurasian milfoil (Myriophyllum spicatum, hereafter referred to as Myriophyllum) is now the most dominant submerged macrophyte. Myriophyllum is a structurally-complex macrophyte with the potential to dramatically alter estuarine food webs through reduced encounter rates between predators and their prey and other mechanisms. Previously, we surveyed faunal communities using throw traps, trawls, cores, and suction sampling to compare milfoil assemblages with other native macrophytes to explore the interactive role of hydrology, diel periodicity, and macrophyte presence in influencing community structure. Here, we use this previously collected data to generate a preliminary food web analyses to determine if milfoil, due to its high complexity, creates a "trophic dead end" and limits higher trophic level production. We found the number of nodes, links, linkage density, and connectance to all be greater in milfoil than Vallisneria americana (hereafter referred to as Vallisneria), indicating that a diverse, productive, and highly connected food web exists in this invasive habitat.